2003
DOI: 10.1152/ajpcell.00006.2003
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1-deficient mice show insulin resistance and defective insulin receptor protein expression in adipose tissue

Abstract: . Caveolin-1-deficient mice show insulin resistance and defective insulin receptor protein expression in adipose tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
254
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(275 citation statements)
references
References 50 publications
19
254
0
2
Order By: Relevance
“…This was correlated with increased expression of PI3K, PKB and p44/42 MAPK activity suggesting a regulatory role for Cav-1 in ozone-induced activation of these signaling pathways. Our findings are in accord with the observation that Cav-1 knockout mice exhibit hyperactivation of PI3K/PKB and p44/42 MAPK (Park et al, 2002;Cohen et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…This was correlated with increased expression of PI3K, PKB and p44/42 MAPK activity suggesting a regulatory role for Cav-1 in ozone-induced activation of these signaling pathways. Our findings are in accord with the observation that Cav-1 knockout mice exhibit hyperactivation of PI3K/PKB and p44/42 MAPK (Park et al, 2002;Cohen et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, introduction of a modification of TC10 that prevents lipid raft association blocks the activation of the G protein by insulin, as well as the stimulation of glucose uptake in fat cells . Targeted disruption of the gene encoding the adipose-enriched raft protein caveolin1 also produced insulin resistance, although it remains uncertain whether this resulted from decreased insulin signaling (Cohen et al, 2003b). Taken together, these data suggest that lipid rafts serve as sites for assembly of signaling complexes that play an important role in insulin action.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have suggested regulatory as well as structural functions for caveolin, which may directly regulate numerous signaling proteins in caveolae (Razani et al, 2002;Cohen et al, 2003b;Ha et al, 2003;Gratton et al, 2004;Kim et al, 2004;Kim and Pak, 2005). Different groups have demonstrated inhibition of G proteins, Src family kinases, nitric oxide synthase, epidermal growth factor receptor, MAP kinase, and protein kinase C by a caveolin scaffolding domain, leading to the suggestion that the biological function of caveolin in caveolae is to suppress cellular signaling (Uttenbogaard et al, 2000;Liu et al, 2002;Razani et al, 2002;Cohen et al, 2003b;Gratton et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Different groups have demonstrated inhibition of G proteins, Src family kinases, nitric oxide synthase, epidermal growth factor receptor, MAP kinase, and protein kinase C by a caveolin scaffolding domain, leading to the suggestion that the biological function of caveolin in caveolae is to suppress cellular signaling (Uttenbogaard et al, 2000;Liu et al, 2002;Razani et al, 2002;Cohen et al, 2003b;Gratton et al, 2004). The specificity of caveolin interaction with these molecules has been confirmed by identifying a common amino acid sequence motif contained in many of these regulatory molecules and in the insulin receptor (IR) as well (Cohen et al, 2003b;Gratton et al, 2004).…”
Section: Introductionmentioning
confidence: 99%